Pengembangan Bahan Ajar Bahasa Arab Berbasis CEFR Untuk Meningkatkan Keterampilan Bahasa Arab Siswa / Development of Arabic Teaching Materials Based on the Common European Framework of Reference (CEFR) to Improve Students' Arabic Language Skills - Habibur Rohman; Faiq Ilham Rosyadi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
In the learning process, teaching materials are one component that has a substantial role in supporting the success of learning. This study aims to develop Arabic teaching materials based on the Common European Framework of Reference (CEFR) level A1 to improve Arabic language skills at MI Darussolihin and to find out how students respond to these teaching materials. This study uses the Borg and Gall model of R & D research which consists of 10 steps, namely potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage trial, product revision, and mass production. . This teaching material product was validated by supervisors, teaching materials experts, CEFR experts, and material experts and responded by 14 students of MI Darussolihin Yogyakarta. The quality of CEFR-based Arabic textbooks based on the assessment of the validator team is in the Good (B) category, with a score of 74.47% of the maximum score of 100%. Students' responses to the quality of these teaching materials are included in the good category (B) with an average score of 10.73 from a maximum score of 12 and an ideal percentage of 89.4% from a maximum score of 100%. The results of product implementation in the broad group also have a positive impact with an average pre-test score of 58 and a post-test score of 69. Based on the results of the study, it can be concluded that this CEFR-based teaching material is feasible to be used as an Arabic language teaching material and is effective for improving students' Arabic language skills. Keywords: Development, Teaching Materials, Common European Framework of Reference (CEFR), Arabic Abstrak Proses dalam pembelajaran, bahan ajar merupakan salah satu komponen yang memiliki peran substansial dalam menunjang keberhasilan pembelajaran. Penelitian ini bertujuan untuk mengembangkan bahan ajar bahasa Arab berbasis Common European Framework of Reference (CEFR) tingkat A1 untuk meningkatkan keterampilan bahasa Arab di MI Darussolihin dan untuk mengetahui bagaimana respon siswa terhadap bahan ajar ini. Penelitian ini menggunakan penelitian R & D model Borg and Gall yang terdiri dari 10 langkah yaitu potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, uji coba produk, revisi produk, uji coba pemakaian, revisi produk, dan produksi masal. Produk bahan ajar ini divalidasi oleh dosen pembimbing, ahli bahan ajar, ahli CEFR, dan ahli materi serta direspon oleh 14 peserta didik MI Darussolihin Yogyakarta. Kualitas buku ajar bahasa Arab berbasis CEFR berdasarkan penilaian tim validator termasuk dalam kategori Baik (B), dengan skor 74,47% dari skor maksimal 100%. Respon tanggapan murid pada kualitas bahan ajar ini termasuk dalam kategori baik (B) dengan skor rata rata 10,73 dari skor maksimal 12 dan persentase keidealan 89,4% dari nilai maksimal 100%. Adapun hasil implementasi produk pada kelompok luas juga berdampak positif dengan nilai rata rata pre test 58 dan nilai post test 69. Berdasarkan hasil penelitian dapat disimpulkan bahwa bahan ajar berbasis CEFR ini layak digunakan sebagai bahan ajar bahasa Arab dan efektif untuk meningkatkan kemampuan bahasa Arab peserta didik. Kata Kunci: Pengembangan, Bahan Ajar, Common European Framework of Reference (CEFR), Bahasa Arab